Multiple and moving bodies: CFD research in an adaptive environment - Ren, Tingrong (Cranfield University, 2000)
During this study a new solution adaptive scheme was developed which applied the structured Adaptive Mesh Refinement (AMR) algorithm directly into a Chimera grid system. Two new Computational Fluid Dynamics (CFD) methodologies, the Chimera grid method and the AMR algorithm, have been successfully integrated. The originality of this study is outlined below. 1).This new scheme integrated the Chimera grid method with the AMR algorithm. By using the Chimera grid method to mesh complicated configurations and then applying the AMR algorithm in different Chimera sub-domains to resolve complicated flow features the advantages of these two methods are combined. 2). Both Graph data structure and orthogonal list storage are employed in this new scheme to describing the Chimera sub-domain relationship and improve the region and point searching efficiency. These methods make this new scheme more flexible and more efficient than existing Chimera grid schemes and AMR schemes. 3). This study extended the application of the AMR algorithm. The main limitation of the Quirk's AMR code, poor geometric packing ability, has been replaced by a versatile Chimera grid scheme. 4). This study improved the accuracy of the Chimera inter-grid communication when simulating supersonic or hypersonic flows with strong discontinuities due to applying the AMR algorithm. 5). The combination of the versatile geometric packing ability of the Chimera grid method and the efficient computation ability of the AMR algorithm makes the current scheme capable of simulating multiple and moving body flow problem with strong discontinuities using moderate computational resources. The material in this thesis documents this development of the Chimera grid scheme with an existing AMR code, and the validation and applications of this scheme. Firstly, a Chimera grid scheme has been developed. Most of the tasks associated with the Chimera grid scheme are performed in a fully automated mode. The graph data structure and orthogonal list storage are used to describe the domain relationships. This allows the sub-domains to be arranged in an arbitrary manner and increases efficiency. Secondly, in order to properly integrate the Chimera grid scheme with the AMR, some modification work on the original AMR code had to be done. This work allowed the Chimera grid scheme to be successfully incorporated into the AMR code. Thirdly, this scheme has been employed to solve time-dependent and steady state shock hydrodynamics problems at supersonic and hypersonic speed. Various validation and application cases, such as, shock reflection, shock diffraction, shock/boundary interaction and multiple moving body flows at supersonic speeds are presented, analysed and compared with experimental results or numerical solutions either from the literature or obtained by using another CFD code. The simulations demonstrate the flexibility of the grid generation and the high efficiency and capability to resolve complex flow features. Finally, future research work arising from the present study has also been discussed and highlighted.